2022
DOI: 10.1007/s40119-022-00262-w
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Atrial Fibrillation Benefit from SAVR with Surgical Ablation Compared to TAVR Alone

Abstract: Introduction:In patients with preoperative atrial fibrillation (AF) undergoing aortic valve replacement, the addition of surgical ablation to surgical aortic valve replacement (SAVR-SA) is efficacious and a Class I guideline. We hypothesized that this subgroup may benefit from SAVR-SA compared to transcatheter aortic valve replacement (TAVR) alone. Methods: Medicare beneficiaries with persistent non-valvular AF who underwent SAVR-SA or TAVR alone between 2012 and 2018 were included. Patients with high-risk sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Combined open procedures show significantly better long-term outcomes than isolated transcatheter aortic valve implantation in elderly patients with low surgical risk and persistent atrial fibrillation. An analysis conducted by William L Patrick et al demonstrates reduced mortality, pacemaker implantation rates, and hospitalizations due to decompensated heart failure in the long-term period for patients who underwent arrhythmia correction and prosthetic valve replacement under cardiopulmonary bypass, compared to the transcatheter aortic valve implantation group (TAVI) group where ablation was not performed [44].…”
Section: Discussionmentioning
confidence: 99%
“…Combined open procedures show significantly better long-term outcomes than isolated transcatheter aortic valve implantation in elderly patients with low surgical risk and persistent atrial fibrillation. An analysis conducted by William L Patrick et al demonstrates reduced mortality, pacemaker implantation rates, and hospitalizations due to decompensated heart failure in the long-term period for patients who underwent arrhythmia correction and prosthetic valve replacement under cardiopulmonary bypass, compared to the transcatheter aortic valve implantation group (TAVI) group where ablation was not performed [44].…”
Section: Discussionmentioning
confidence: 99%
“…tion ablation with a MAZE procedure. Recent data have shown that patients with severe AS and persistent AF who undergo SAVR or TAVR without AF ablation have a higher risk of long-term mortality [91].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients with chronic atrial fibrillation may also benefit from surgery by undergoing concomitant atrial fibrillation ablation with a MAZE procedure. Recent data have shown that patients with severe AS and persistent AF who undergo SAVR or TAVR without AF ablation have a higher risk of long-term mortality [ 91 ].…”
Section: Need For Concomitant Proceduresmentioning
confidence: 99%